PENGUATAN USAHA PENGRAJIN BANDENG PRESTO KECAMATAN PEDURUNGAN SEBAGAI UPAYA MENUJU KEBERDAYAAN DAN KEMANDIRIAN USAHA - Yani Prihati; Sinta Tridian Galih; Tri Karyanti (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Presto milkfish is one of the special foods and has even become an icon of Semarang. Presto milk processing business in micro, small, medium to large scale in many places in Semarang and one of them is a craftsman of Presto milkfish Bu Joko and Bu Hari in Kecamatan Pedurungan. The data states that the existing MSMEs in Indonesia contribute considerably to the state. Even so, MSMEs tend to be vulnerable to pressure from both internal and external parties so that in order to survive and develop in the era of MEA, needed support  from the government especially related to capital, market access and business licensing. The problems encountered by adding product varians, providing milk vacuum equipment, developing the web to market products online, organizing socialization and assisting in the handling of Household Food License (PIRT) and redesigning product packaging to be more informative for consumers and able to maintain durability product. With solutions implemented in this program, the Presto Milkfish Craftsmen in Kecamatan Pedurungan have small business empowerment measured through 3 indicators of business access, market access and technology access. With the improvement of management in the form of PIRT has been obtained, the availability of production equipment technology and has the availability of marketing media and ordering web, the craftsmen milkfish Presto in Kecamatan Pedurungan have the independence of business because it can meet the needs by relying on the ability and own strength to run the business.Keywords: milkfish craftsman, empowerment, business independence